Optimising management of patients with heart failure with preserved ejection fraction in primary care (OPTIMISE-HFpEF): rationale and protocol for a multi-method study - Forsyth, F; Mant, J; Taylor, C; Hobbs, F; Long, A (Royal College of General Practitioners, 2019)
Background Heart failure with preserved ejection fraction (HFpEF) is less well understood than heart failure with reduced ejection fraction (HFrEF), with greater diagnostic difficulty and management uncertainty. Aim The primary aim is to develop an optimised programme that is informed by the needs and experiences of people with HFpEF and healthcare providers. This article presents the rationale and protocol for the Optimising Management of Patients with Heart Failure with Preserved Ejection Fraction in Primary Care (OPTIMISE-HFpEF) research programme. Design & setting This is a multi-method programme of research conducted in the UK. Method OPTIMISE-HFpEF is a multi-site programme of research with three distinct work packages (WPs). WP1 is a systematic review of heart failure disease management programmes (HF-DMPs) tested in patients with HFpEF. WP2 has three components (a, b, c) that enable the characteristics, needs, and experiences of people with HFpEF, their carers, and healthcare providers to be understood. Qualitative enquiry (WP2a) with patients and providers will be conducted in three UK sites exploring patient and provider perspectives, with an additional qualitative component (WP2c) in one site to focus on transitions in care and carer perspectives. A longitudinal cohort study (WP2b), recruiting from four UK sites, will allow patients to be characterised and their illness trajectory observed across 1 year of follow-up. Finally, WP3 will synthesise the findings and conduct work to gain consensus on how best to identify and manage this patient group. Results Results from the four work packages will be synthesised to produce a summary of key learning points and possible solutions (optimised programme) which will be presented to a broad spectrum of stakeholders to gain consensus on a way forward. Conclusion HFpEF is often described as the greatest unmet need in cardiology. The OPTIMISE-HFpEF programme aims to address this need in primary care, which is arguably the most appropriate setting for managing HFpEF.